Silvopastoral System Economical and Financial feasibility with Jatropha curcas L. in Manabí, Ecuador - Diana Rade L (Revista MVZ Córdoba, 2017)
Objective. To assess the economic and financial feasibility of traditional silvopastoral systems for the biofuels production as a contribution to the sustainability of “Piñón for Galapagos” project. Materials and methods. A survey was conducted to 450 small livestock producer in 10 cantons of the Manabí province in order to collect basic agronomic knowledge, management, establishment and costs involved in production of the Piñón ((Jatropha curcas L.)/Savoy (Megathyrsus maximus) silvopastoral systems. For Piñón CP041 production recording plantation in live fence were stablished and for the tradition Piñón, the production of 10 sites were recorded, both systems since 2009. With those data were calculated the following economic indicators: ratio benefit/cost, net present value (NPV), internal rate ratio (IRR) and land expectation value (LEV). Results. The study exhibited a production decrease of Piñón with the passage of time. The CP041 INIAP improved silvopastoral system Piñón showed a B/C 1.07, NPV of USD$ 404.11, LEV US$ 970.23 and IRR of 18%. Followed by silvopastoral system with a local Piñón with a B/C 1.06, NPV of USD$ 363.66, LEV USD$ 873.10 and IRR of 17% and finally silvopastoral system without harvesting Piñón with a B/C 1.05, NPV of USD$ 285.72, LEV USD$ 685.99 and IRR of 15%. Conclusions. The alternative biofuels production was the silvopastoral systems (INIAP CP041)/Savoya in Manabí and is economically feasible. This system does not compete for arable land for food production and would not affect food security.